Meningkatkan Keterampilan Tari Sulanjana Siswa Melalui Metode Demontrasi - Sucia Panca Lestari; Geri Syahril Sidik; Agus Akhmad Wakih (Pusat Riset dan Inovasi Nasional, 2024)
The background to this research is the low level of dance skills of students in class IV of Mugarsari Elementary School, Tasikmalaya City. This research aims to determine and analyze the planning, implementation and improvement of students' dance skills using the demonstration method. The method used in this research is Classroom Action Research (PTK) with the object of this research being 29 students. The PTK model used is the PTK research method according to Kemmis and Mc. Taggart which consists of planning, action, observation and reflection in each cycle. The discussion of this research uses the demonstration method in the dance learning process by carrying out tests at the end of each cycle. Data collection techniques in this research are by means of observation, tests and documentation. The results of the research concluded that learning dance using the demonstration method was able to improve students' skills in learning dance. This increase before using the demonstration method (Pre-action) obtained an average score of 79.7% with a completeness percentage of 22.7% in the